Eco-Homestay: Development Concept On Rural Tourism-Based Conservation Model (Study Case of Sidomulyo Village, Silo District, Jember Regency) - Asbullah, Alvan Sidiq; Irhamsyah, Muhammad Syuhada; Nugraha, Muhammad (Graduate School, Universitas Brawijaya, 2013)
The purposes of this research were to assess the concept of Eco-Homestay in conservation-based tourism in rural area. A case study was set up at Sidomulyo Village, Silo District, Jember. A qualitative method in the form of in-depth interviews was performed as a tool to generate models. Informants in this study included the staff of the Department of Forestry and Plantation, lecturer of the Faculty of Agriculture and Polytechnic of Jember, State University of Jember, and Sidomulyo community in Silo Districts, Jember. The result showed that the purposes of eco-homestay can be reached by managing the structure of integrated development, structure of organizational management, structure of financial management, marketing strategies, operational strategies and physical building. Keywords: conservation, eco-homestay, rural tourism, Sidomulyo